Sex-Specific Changes in Gut Microbiome Composition following Blueberry Consumption in C57BL/6J Mice - Wankhade, Umesh D. (Nutrients, 2019)
The antioxidant and anti-inflammatory properties of blueberries improve vascular function and insulin sensitivity. However, the bioavailability of the active compounds in blueberries is largely dependent on the gut microbiota, which may themselves be altered by blueberry components. The objective of the current study was to explore a possible sex-dependent modulation of the gut microbiota following supplementation with blueberries in adult mice. Eight-week-old C57BL/6J mice (n = 7–10/group) were provided with control or blueberry-containing diets (5% freeze-dried powder) for 4 weeks. Body weight, composition, and food intake were measured weekly. Genomic DNA was isolated from the cecal contents for 16S rRNA sequencing. Blueberry feeding decreased α-diversity (operational taxonomical unit abundance) and altered β-diversity (p < 0.05). At the phylum level, the Firmicutes to Bacteroidetes ratio was significantly lower in the blueberry-fed groups (p < 0.001), along with increased Tenericutes and decreased Deferribacteres. At the genus level, blueberry feeding led to sexually-dimorphic differences, which were associated with predicted metabolic pathways. Pathways such as fatty acid and lipid metabolism were significantly different and demonstrated a stronger association with microbes in the male. To summarize, blueberry supplementation led to sexually-dimorphic global changes in the gut microbiome, which could possibly contribute to physiological changes in mice.